ANALISIS YURIDIS PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA NARKOTIKA GOLONGAN I BUKAN TANAMAN - Telaumbanua, Yarioni Grace (LPPM Universitas Nias Raya, 2025)
Narcotics refer to substances or drugs derived from either plant or non-plant sources, including synthetic or semi-synthetic compounds, which induce decreased consciousness, loss of taste, pain reduction or elimination, and potential dependency in users. Although Law Number 35 of 2009 concerning Narcotics has categorized narcotics into several groups and has regulated the issue of narcotics, crimes associated with narcotics remain prevalent. The objective of this study is to conduct a juridical analysis of the punishment imposed on perpetrators of class I non-plant narcotics crimes. The research methodology employed is normative research, which involves examining library materials, also known as library research. Secondary data sources, encompassing primary legal materials, secondary legal materials, and tertiary legal materials, were utilized for this study to acquire relevant theories, concepts, legal principles, and regulations. Based on the research findings and subsequent discussion, it can be inferred that the judge's decision to sentence the accused perpetrator of narcotics abuse (Study Decision Number 79/Pid.Sus/2023/PN Gst) to prison was deemed incorrect. This discrepancy arises from the fact that the panel of judges failed to consider Article 103 Paragraph (1) letter a of Law Number 35 of 2009 concerning Narcotics, which mandates the decision to order treatment and/or rehabilitation for the individual concerned if proven guilty of committing a narcotics crime.